2016
DOI: 10.1589/jpts.28.162
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration, skeletal muscle damage and inflammation before the competitions among the elite wrestlers

Abstract: [Purpose] The present study aimed to identify weight-loss and hydration levels before competitions among elite wrestlers and determine the skeletal muscle damage and inflammation levels after dehydration. [Subjects] Seventy-two elite wrestlers who participated in the Turkish Wrestling Championship. [Methods] With the help of specialists, 5 cc of blood were drawn from the forearm veins of the wrestlers. Laboratory analyses of Na+, BUN, Glucose, CK, LDH, AST, ALT, C-RP levels were performed. Using a mathematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Ozkan and Ibrahim [30] also measured alterations to CK levels as a consequence of weight reduction, reporting results similar to those of Isik et al [29]. Ten wrestlers lost > 5% of their body weight by undergoing dehydration as their RWL method.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Ozkan and Ibrahim [30] also measured alterations to CK levels as a consequence of weight reduction, reporting results similar to those of Isik et al [29]. Ten wrestlers lost > 5% of their body weight by undergoing dehydration as their RWL method.…”
Section: Discussionsupporting
confidence: 60%
“…Further studies should elaborate how different methods may lead to different levels of muscle damage, as suggested by those studies that focused on body weight loss due to dehydration methods [29,30]. Based on our data, we are unable to confirm the degree to which RWL caused MD and to what degree exercise contributed to it.…”
Section: Discussionmentioning
confidence: 62%
“…It is well documented that athletes perform better than untrained; especially in the specific sport they compete in [27][28][29]. In addition, athletes, as well as other trained populations, present with faster and more efficient recovery from physical activity [30][31].…”
Section: Variable Wrestlers Untrainedmentioning
confidence: 99%
“…It is difficult to discourage athletes from these practices, but they can be made aware, if there is evidence that such practices could affect their muscular functioning [3]. To explain this muscular damage, studies have been carried out on elite fighters and in healthy elite and amateur athletes who were evaluated after intensive exercise until muscular exhaustion, causing an elevation of cardiac biomarkers in 62% of the subjects like troponin, a possible indicator of heart damage, acute coronary syndrome, or even infarction [4][5][6][7][8][9][10][11]. Wrestlers were divided into groups, depending on their hydration levels, and it was concluded that the levels of inflammation and markers of muscle damage (creatine phosphokinase, CPK, lactate dehydrogenase, LDH, and aspartate transaminase, AST) obtained in their post-competition blood samples were different between both groups and higher in the forearm muscles of the dehydrated group.…”
Section: Introductionmentioning
confidence: 99%